Long‐term opioid therapy for chronic non‐cancer pain in Germany. (22nd October 2015) - Marschall, U.; L'hoest, H.; Radbruch, L.; Häuser, W.
Abstract: Background: No data are available on the prevalence and predictors of (high‐dose) long‐term opioid therapy (LTOT) and on abuse/addiction of prescribed opioids by patients with chronic non‐cancer pain (CNCP) outside North America and Scandinavia. Methods: We analysed randomly selected claims records of 870, 000 persons (10% of insureds) in a large German medical health insurance organization during the fiscal year 2012. Results: The prevalence of LTOT prescriptions (defined by at least one opioid prescription per quarter for at least three consecutive quarters) for CNCP was 1.3% of all insureds. The mean daily dosage of LTOT was 58 (SD 79; minimum 0.3, maximum 2010) mg morphine equivalent/day. The percentage of insureds with high‐dose opioid prescriptions (≥100 mg morphine equivalent/day) among LTOT insureds was 15.5%. High‐dose LTOT (compared to traditional dose) prescription was associated with younger age, male gender, diagnoses of chronic pain disease, somatoform pain disorder, depression and prescription of anticonvulsants. The pooled 1‐year prevalence of abuse/addiction of prescribed opioids (defined by hospital stays because of mental and behavioural disorders due to alcohol, opioids, tranquilizers, multiple substances and intoxications by narcotic agents) was 0.008%. Abuse/addiction of prescribed opioids was associated with younger age, diagnoses of somatoform pain disorder, depression and prescription of tranquilizers. Conclusions: The study found no signals of an 'opioid epidemic' in Germany. However, careful selection of patients with CNCP considered for LTOT and continuous evaluation during LTOT are warranted.